2013
DOI: 10.1242/jcs.119917
|View full text |Cite
|
Sign up to set email alerts
|

Six1 regulates proliferation of Pax7+ muscle progenitors in zebrafish

Abstract: SummaryIn the embryonic zebrafish, skeletal muscle fibres are formed from muscle progenitors in the paraxial mesoderm. The embryonic myotome is mostly constituted of fast-twitch-specific fibres, which are formed from a fast-specific progenitor cell pool. The most lateral fraction of the fast domain in the myotome of zebrafish embryos derives from the Pax7-positive dermomyotome-like cells. In this study, we show that two genes, belonging to the sine oculus class 1 (six1) genes (six1a and six1b), are both essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 51 publications
5
24
0
Order By: Relevance
“…2C, red arrows), and that the overall cross-sectional diameter was decreased (Fig. 2D, inset), which is consistent with what has been previously reported using a splice-blocking six1a MO (Nord et al, 2013). In addition, loss of the ability to refract polarized light (birefringence) demonstrated that six1a knockdown led to irregular muscle fiber arrangement (Fig.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…2C, red arrows), and that the overall cross-sectional diameter was decreased (Fig. 2D, inset), which is consistent with what has been previously reported using a splice-blocking six1a MO (Nord et al, 2013). In addition, loss of the ability to refract polarized light (birefringence) demonstrated that six1a knockdown led to irregular muscle fiber arrangement (Fig.…”
Section: Introductionsupporting
confidence: 90%
“…During early myogenesis, knockdown of mouse and zebrafish Six1 results in severe muscle hypoplasia and a decrease in fast-twitch fibers (Bessarab et al, 2008;Grifone et al, 2005;Laclef et al, 2003a;Nord et al, 2013), demonstrating a role for Six1 in both muscle progenitor activation and the promotion of fast muscle differentiation. However, overexpression of Six1 in zebrafish also prevents fast twitch fiber formation (Nord et al, 2013), indicating that improper Six1 levels, either too high or low, can negatively affect early muscle differentiation. To date, mechanisms controlling Six1 expression during embryogenesis have not been elucidated in any tissue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SIX1 expression level is increased in embryogenesis and promotes progenitor cell expansion and survival (6)(7)(8). SIX1 absence results in the reduction in size or loss of numerous organs, as a result of inhibited proliferation and increased apoptosis in mice (9).…”
Section: Introductionmentioning
confidence: 99%